Applying the information acceptance model to predict purchase intention in social media - Richard Tjongirin; Matthew Gianto; Sabrina Sihombing (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
E-WOM has become an essential marketing tool, as an online marketplace compete to dominate the online space. This paper assesses the relationship of e-WOM and its relationship towards purchase intention. The theoretical model based on the information acceptance model suggesting information (quality, credibility, usefulness, and adoption), needs of information and attitude towards information are the primary variables that influence purchase intention. This is a descriptive research; closed-ended questionnaires were distributed with 294 respondents with college students as the main demographic. The findings of this research show that the usefulness of information does play a significant influence toward purchase intention, but the attitude towards information does not significantly influence information usefulness. This study implies that some companies which compete in the online space should primarily focus on how useful their information is deemed by the consumers.